Perancangan cold storage pada kapal nelayan tradisional terhadap penekanan biaya operasional dan kualitas ikan - Sungkono; Juhana Said (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
This study takes the case of traditional fishing boats in the Beba Fish Landing Base, Takalar Regency, South Sulawesi. These fishing boats still use conventional fish catch shelters. This method is expensive and risks the quality of fish freshness and even damage to the caught fish. To overcome the problem, a cold storage design is carried out as a place to store fish catches. This study aims to 1) design a cold storage with a capacity of 1 ton of fish with a cooling temperature of 2 - 0°C; 2) calculate the required power and cost; 3) calculate Break Even Point (BEP). The results of this study obtained a cold storage design with dimensions of 248.2 cm x 120.4 cm and a height of 84 cm. The inner and outer walls of cold storage are made of stainless material, while the middle of the Styrofoam is an insulating material. The refrigerant used is R 134 a. Indoor cooling using an air misting system. Cold Storage power 593 Watt at 220 Volt AC voltage. The cost of making 1 cold storage unit is IDR 22.350.000 and the power of a 1 hp generator is IDR 4.000.000, so the total is IDR 26.350.000. Break Even Point (BEP) from the draft is 9,4 months. The results of this design and, maintaining the freshness fish, also reduce the operational costs of traditional fishers.